Analisis preferensi risiko dan variabilitas pendapatan petani karet di Kecamatan Muara Tabir, Kabupaten Tebo - Susridar Susridar; Irawan Wibisonya; Dwinita Agustiana; Ayu Putri Merry Anisya (Journal of Agribusiness Science and Rural Development, 2026)
The plantation sector in Jambi Province is a mainstay sub-sector in economic development, especially for rubber commodities. Rubber is a crop that has been cultivated by the people of Jambi Province as a main livelihood. Smallholder plantations generally produce rubber in the form of processed rubber (bokar). This research was conducted in January-February 2025. Respondents used in this study using a census method totaling 42 people with the categories of low-quality and high-quality Bokar farmers. Data analysis used farmer preference analysis with a farmer income utility approach as well as income analysis and coefficient of variation analysis to determine the level of risk of farmer income. The overall estimation results show that farmer risk preferences for all inputs, both sales in the form of low-quality and high-quality bokar, indicate that all rubber farmers in the study location are risk takers. Judging from the average value of the overall AR shows that the level of preference of low-quality bokar farmers is -0.0026 while the preference of high-quality bokar farmers is -0.00711. Farmers are more likely to have a risk-taking nature. This is because in general, farmers get a relatively stable selling price. In this study, the average farmer income generally shows that the income per hectare for low-quality Bokar is recorded at around Rp 10,396,643, while the average income per farmer for high-quality Bokar reaches Rp 33,726,429. At the risk level, it shows that the level of risk of rubber farmers' income in Muara Tabir District is relatively low, this can be shown by the high-quality Bokar coefficient value of 0.3394 which is greater than the low-quality Bokar coefficient value of 0.2091.